Evaluation of Exotic Genotypes under Controlled Drought Conditions at Reproductive Phase (Bangladesh Rice Journal, 2025)
A study was conducted in the Plant Physiology Division, Bangladesh Rice Research Institute (BRRI), Gazipur during T.Aman seasons, 2018 to evaluate the genotypes collected from India under controlled drought conditions. Seven genotypes (CR Boro Dhan 2 (CR-898), CR Dhan 300, CR Dhan 10, Naveen, CR Sugangh Dhan 907, Geetanjali, and DRR Dhan 44) along with drought tolerant check BRRI dhan56, BRRI dhan71 and susceptible check IR64 were tested. Regarding growth characteristics genotype x treatment interaction effect was not significant but plant height, tiller number and straw weight were reduced due to drought stress indicating growth was arrested by drought stress. A similar observation was also found in panicle number. Under drought stress, more than 90% of panicle could exert fully only in CR Sugangh Dhan 907 and DRR Dhan 44 among the exotic genotypes which also showed 44.1% and 39.0% yield reduction respectively compared to control plants. The grain yield reduction was mainly due to increased percent sterility (41.4% and 33.4% respectively) under stress conditions. Below 30 cm soil depth, the highest cumulative root length (CRL) was found in CR Sugangh Dhan 907 and DRR Dhan 44. DRR Dhan 44 also had the highest root length density (RLD) (0.73 cm cm-3) and root weight density (RWD) (0.44 mg cm-3). The exotic genotype DRR Dhan 44 produced the highest amount of root (572.7 mg) per gram of shoot. The results suggested that genotypes DRR Dhan 44 and CR Sugangh Dhan 907 appear to be suitable for cultivation in drought-prone areas and these could be used for the development of drought-tolerant variety as donor parents in the hybridization program.Bangladesh Rice J.27(1): 1-11, 2023